Phylogenetic divergence of fish and mammalian metallothionein: Relationships with structural diversification and organismal temperature - CAPASSO C.; CARGINALE V.; PARISI E.; SCUDIERO, ROSARIA; CRESCENZI, ORLANDO; SPADACCINI, ROBERTA; TEMUSSI, PIERO ANDREA (Journal of Molecular Evolution, 2003)
Metallothioneins (MTs) are nonenzymatic low molecular weight proteins, that play an important role in the homeostasis and detoxification of heavy metals in a large variety of organisms. These proteins are endowed with striking features, including an unusual amino acid composition characterized by the presence of 20 cysteines out of a total of 60 residues and absence of secondary structure elements. It is generally accepted that MTs underwent few modifications during evolution because of these structural and functional constraints. Such a conclusion is founded on the studies carried out mostly on MTs of mammalian origin. For such a reason, we have decided to compare the MTs of homeothermic and poikilothermic organisms, such as mammals and fish, with the specific aim to put in relation phylogenetic divergence and structural/functional adaptation to temperature. We have included in our analysis also Antarctic Notothenioids, a fish group characterized by genetic isolation and cold-adaptation to a particular harsh environment. We have determined the average hydropathic index of ancestral MT sequences and used them to infer the temperatures of the environment housing the hypothetical ancestor organisms. Finally, we have derived phylogenetic relationships of MT molecules from the pairwise comparison of their three-dimensional structures.